2012
DOI: 10.1097/bth.0b013e3182388561
|View full text |Cite
|
Sign up to set email alerts
|

Flexor Tendon Retrieval in Zone I and II

Abstract: In this article we set out to describe a simple and modified Sourmelis technique for tendon retrieval in zone I and II. In this modified technique, a long loop of nylon suture is used and hence there is no need for the stage 4 of Sourmelis technique. The purpose of this paper is to illustrate this modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Karbalaeikhani and Yavari 34 used a long loop of nylon suture to connect the proximal stump that was left in situ to the feeding tube. The tube is delivered distally, pulling on the tendon and retrieving it distally as well.…”
Section: Resultsmentioning
confidence: 99%
“…Karbalaeikhani and Yavari 34 used a long loop of nylon suture to connect the proximal stump that was left in situ to the feeding tube. The tube is delivered distally, pulling on the tendon and retrieving it distally as well.…”
Section: Resultsmentioning
confidence: 99%
“…Agreed with the current evidence, in this study, most respondents (85%) supported atraumatic tendon retrieval, and reported a variety of retrieval techniques. Recent development of flexor tendon retrieval techniques advocated the use of sutures, a flexible tube and a proximal palmar incision, in which the tendon stump was connected to the flexible tube and successfully retrieved through the tendon sheath (5)(6)(7)(8). Most respondents (45%) mentioned the use of sutures and a flexible feeding tube, and some respondents (10%) also mentioned the creation of an extra incision.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a wealth of research in the field, management of hand flexor tendon injury remains inconsistent in approaches and outcomes (3). Current evidence revealed several beneficial development and change in practice in the field, including the use of wideawake local anesthesia no tourniquet (WALANT) technique (4), updated methods of retrieving the retracted tendon stump (5)(6)(7)(8), change in tendon repair approaches (9), the use of early active mobilization in post-surgery rehabilitation (10).…”
Section: Introductionmentioning
confidence: 99%